2012
DOI: 10.3345/kjp.2012.55.12.470
|View full text |Cite
|
Sign up to set email alerts
|

Detection rate and clinical impact of respiratory viruses in children with Kawasaki disease

Abstract: PurposeThe purpose of this prospective case-control study was to survey the detection rate of respiratory viruses in children with Kawasaki disease (KD) by using multiplex reverse transcriptase-polymerase chain reaction (RT-PCR), and to investigate the clinical implications of the prevalence of respiratory viruses during the acute phase of KD.MethodsRT-PCR assays were carried out to screen for the presence of respiratory syncytial virus A and B, adenovirus, rhinovirus, parainfluenza viruses 1 to 4, influenza v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 12 publications
1
34
0
4
Order By: Relevance
“…In a child with clinical findings compatible with classic KD, the detection of respiratory viruses such as respiratory syncytial virus, metapneumovirus, coronaviruses, parainfluenza viruses, or influenza viruses does not exclude the diagnosis of KD. [86][87][88] The detection of adenovirus in a nasopharyngeal sample from a patient with suspected KD poses a particular challenge, because the illnesses have some similar clinical features. 89 Adenoviruses (particularly species C) can persist in tonsil or adenoid tissue, potentially confusing diagnosis of a subsequent febrile illness.…”
Section: Conjunctivitismentioning
confidence: 99%
“…In a child with clinical findings compatible with classic KD, the detection of respiratory viruses such as respiratory syncytial virus, metapneumovirus, coronaviruses, parainfluenza viruses, or influenza viruses does not exclude the diagnosis of KD. [86][87][88] The detection of adenovirus in a nasopharyngeal sample from a patient with suspected KD poses a particular challenge, because the illnesses have some similar clinical features. 89 Adenoviruses (particularly species C) can persist in tonsil or adenoid tissue, potentially confusing diagnosis of a subsequent febrile illness.…”
Section: Conjunctivitismentioning
confidence: 99%
“…Using multiplex real-time-polymerase chain reaction (PCR), Cho et al18) also revealed that 22% of acute KD patients tested positive for more than one of 11 respiratory viruses {RSV; adenovirus; rhinovirus; parainfluenza viruses 1 and 3; influenza viruses A and B; human metapneumo virus; human bocavirus; and human coronavirus (OC43/229E, NL63)} 18). However, these rates of viral infection showed no differences between acute KD patients and febrile patients without KD in a small case-control study (32.7% in 55 acute KD patients versus 30.8% in 78 febrile patients without KD) using a multiplex real-time-PCR assay 19). These reports support the hypothesis that various infectious agents are involved in the onset of KD, but do not cause KD directly 2)14)…”
Section: Discussionmentioning
confidence: 90%
“…A recent article also reported a case of KD associated with parainfluenza type 3 viral infection, 45 and another article reported adenovirus detection in some KD cases. 46 However, Kim et al 47 reported that there was no significant association between the presence of any of the 15 respiratory viruses and the incidence of KD. New tests or techniques for specific microorganisms may help us find the etiology of KD.…”
Section: Discussionmentioning
confidence: 99%